Mercury levels in human population from a mining district in Western Colombia (2018)
A biomonitoring study was carried out to examine the adverse impacts of total mercury in the blood (HgB), urine (HgU) and human scalp hair (HgH) on the residents of a mining district in Colombia. Representative biological samples (scalp hair, urine and blood) were collected from volunteered participants (n = 63) to estimate the exposure levels of THg using a Direct mercury analyzer. The geometric mean of THg concentrations in the hair, urine and blood of males were 15.98. μg/g, 23.89. μg/L and 11.29. μg/L respectively, whereas the females presented values of 8.55. μg/g, 5.37. μg/L and 8.80. μg/L. Chronic urinary Hg (HgU) levels observed in male workers (32.53. μg/L) are attributed to their long termed exposures to inorganic and metallic mercury from gold panning activities. On an average, the levels of THg are increasing from blood (10.05. μg/L) to hair (12.27. μg/g) to urine (14.63. μg/L). Significant positive correlation was found between hair and blood urinary levels in both male and female individuals. Thus the present biomonitoring investigation to evaluate the Hg levels and associated health issues would positively form a framework for further developmental plans and policies in building an ecofriendly ecosystem. © 2017.